Crossdocking Distribution Networks with Setup Cost and Time Window Constraint - MA, Hong (Institutional Knowledge at Singapore Management University, 2011)
In this work, we study a new shipment consolidation and transportation problem in crossdocking distribution networks that considers trade-offs between transportation costs, inventory and time scheduling requirements. Transportation costs include time costs, truck setup costs, and the number of trucks used. The model is formulated as an integer program, and shown to be in the strong sense. Moreover, a solution approach is provided which consists of two stages. First, a reduced problem is solved for a truckload transportation plan. This is followed by a heuristic solution approach to the remaining less-than-truckload problem. Computational experiments are conducted to test the effectiveness and efficiency of the heuristics. The various cost parameters and time window settings of the distribution network are also discussed.